Characterization of LIC11207, a novel leptospiral protein that is recognized by human convalescent sera and prevents apoptosis of polymorphonuclear leukocytes - Prêtre, Gabriela (2013)
We report the study of a predicted outer-membrane leptospiral protein encoded by the gene lic11207. This protein is conserved in several pathogenic leptospiral strains but is absent in the saprophyte Leptospira biflexa. This putative outer-membrane protein has a domain of unknown function (DUF) 1565 found in several phylogenetically diverse bacteria and in the archaeon Methanosarcina acetivorans. The gene was cloned and expressed in Escherichia coli BL21 (SI) strain using the expression vector pDEST17. The 34 kDa recombinant protein was tagged with N-terminal hexahistidine and purified by metal-charged chromatography. The purified protein was used to assess: reactivity with human convalescent sera; in vivo expression; ability to activate endothelial cells (EC); and ability to modulate the apoptosis of polymorphonuclear cells (PMNs). The LIC11207 coding sequence was identified in vivo in the hamster renal tubules during experimental infection with Leptospira interrogans. The rLIC11207 showed significant antigenicity against human convalescent sera when compared with sera from healthy donors. The recombinant protein did not alter the surface expression of E-selectin or intercellular adhesion molecule 1 (ICAM-1) in EC and failed to induce the release of von Willebrand factor (vWF). Interestingly, rLIC11207 delayed apoptosis of PMNs suggesting a possible role of this protein during the infection. © 2012 Elsevier Ltd.